Kajian Histologis Infeksi LD50 SLNPV terhadap Kerusakan Membran Peritrofik Larva Spodoptera litura Fabricius - Yayan Sanjaya; Nanin Diah; Wardono Niloperbowo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
The effect of SlNPV infection on  peritrophic membrane  of Spodoptera litura has been carried out. The damage of histological structure caused by SlNPV (0, 315, 390, 465, 540 and 615 PIB/ml) was investigated after 0, 12, 24 ,72 and 96 hours post infection. The histological material was prepared by using parafin method after fixation with Bouin Solution, then sliced into 7 mm and stained with Hematoxilin-Eosin.   The descriptive obsevation on structural intact of peritrophic membrane histology caused by SlNPV infection shows a tendency to decrease, while in control, there was no damage at all.  The longer the exposition of virion in the midgut lumen the more damage on peritrophic membrane occurred. The severest damage occurred 96 hour after infection. The result prove that haNPV virion can destroy histological structure of midgut